PENGARUH FINANCIAL DISTRESS DAN FAKTOR LAINNYA TERHADAP AUDIT REPORT LAG - RADJAH, NADINE VIRQUITA ECHICO; GUNAWAN, HERY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to obtain empirical evidence about the effect of firm size, profitability, leverage, audit reputation, subsidiaries, and financial distress as independent variables to audit report lag as dependent variable. The population in this research is cyclicals consumer and non-cyclicals consumer companies that listed in Indonesia Stock Exchange (BEI) from 2020-2022. The sample used for this research consist of 73 listed cyclicals consumer and non-cyclicals consumer companies. The selection of these sample used the purposive sampling method with total 219 research data and the data analysis method in this research is used multiple regression analysis. The result in this research indicated that audit reputation had effect to audit report lag. While firm size, profitability, leverage, subsidiaries, and financial distress had no effect to audit report lag.